Visualization of microvascular angiogenesis using dual-frequency contrast enhanced acoustic angiography: a review - Newsome, Isabel G. (Ultrasound Med Biol, 2020)
Cancerous tumor growth is associated with the development of tortuous, chaotic microvasculature, and this aberrant microvascular morphology can act as a biomarker of malignant disease. Acoustic angiography is a contrast-enhanced ultrasound technique that relies on superharmonic imaging to form high-resolution, three-dimensional maps of the microvasculature. To date, acoustic angiography has been performed with dual-element transducers that can achieve high contrast-to-tissue ratio and resolution in preclinical small animal models. In this review, we first describe the development of acoustic angiography, including the principle, transducer design, and optimization of superharmonic imaging techniques. We then detail several preclinical applications of this microvascular imaging method, as well as the current and future development of acoustic angiography as a preclinical and clinical diagnostic tool.